Toxicity and enzymatic inhibitory action of Spirulina sp. and Nostoc muscorum extracts on detoxifying enzymes in Spodoptera frugiperda (J. E. Smith) (Noctuidae: Lepidoptera) - Chinnappa Hallikeri Sharanappa; Mallappa Bheemanna; Aralimarad Prabhuraj; Naik Rathod Harischandra; Mohan Naik Nagaraj; Narsing Rao Saroja; Bheeranna Kariyanna (Acta Scientiarum. Biological Sciences, 2024)
The fall armyworm (FAW) Spodoptera frugiperda is a destructive insect pest that belongs to the Noctuidae family and Lepidoptera order. It is a polyphagous pest that harms economically significant cereals and many vegetable crops. This pest has developed resistance to most of the synthetic insecticides through increasing enzymatic activity, so there is a need to take action to prevent the resistance development and damage caused by this pest. A laboratory study on the efficacy of Spirulina sp. and Nostoc muscorum extracts against S. frugiperda was tested using four different solvents: hexane, petroleum ether, ethanol and methanol. The results revealed that N. muscorum hexane and petroleum ether extract recorded the lowest LC50 values of 133.18 and 165.68 ppm, respectively. This was followed by Spirulina hexane and petroleum ether extract, with LC50 values of 337.28 and 468.05, ppm respectively. The results of the study of enzymatic inhibitory action of cyanobacterial extracts showed that Nostoc muscorum hexane and petroleum ether extract significantly decreased the activity of esterase, glutathione S-transferase and cytochrome p450 with a mean of 0.29 and 0.36 µmoles of naphthol min-1 µg-1 of protein, 1.30 and 1.40 µmoles of CDNB min-1 µg-1 of protein and 0.28 and 0.38 µmoles of p-nitroanisole min-1 µg-1 of protein respectively. This was followed by Spirulina hexane extract with a mean of 0.69 naphthol min-1 µg-1 of protein, 1.48 µmoles of CDNB min-1 µg-1 of protein and 0.46 p-nitroanisole min-1 µg-1 of protein respectively and control population significantly recorded higher enzymatic activities. Spirulina sp. and N. muscorum extracts were having a significant effect on larval mortality and inhibiting the detoxifying enzyme activity. These findings demonstrate the potential of cyanobacterial extracts as an innovative strategy against S. frugiperda and suggest that this may helpful in managing insecticide resistance.